Longitudinal Associations Between Dysfunctional Maltreatment‐Related Cognitions and Psychopathology in Children and Adolescents. Issue 4 (10th July 2019) - de Haan, Anke; Keller, Ferdinand; Ganser, Helene G.; Münzer, Annika; Witt, Andreas; Goldbeck, Lutz
Abstract: Dysfunctional posttraumatic cognitions seem to play an important role in adjustment after traumatic experiences. However, little research has been done on maltreated children and adolescents. Furthermore, possible causal associations between cognitions, posttraumatic stress symptoms, and internalizing and externalizing problems have rarely been investigated. In the current study, 263 maltreated children and adolescents (8–17 years of age) were assessed at baseline and again at time points 6 and either 12 or 18 months later. Cross‐lagged panel analyses were used to gain a better understanding of the course of and associations among dysfunctional maltreatment‐related cognitions, posttraumatic stress symptoms, and internalizing and externalizing problems. Ratings of all variables significantly decreased over time. Moderate to strong autoregressive paths emerged for all variables, denoting stability. Furthermore, the variables showed moderate to high correlations at every assessment. Posttraumatic stress symptoms moderately predicted dysfunctional maltreatment‐related cognitions as well as internalizing and externalizing problems 6 months after baseline. Cross‐lagged paths from the cognitions as well as from internalizing and externalizing problems to all other variables were not significant. Age, gender, and maltreatment characteristics did not play a relevant role in these cross‐lagged associations when they were included as covariates. Our results underline the cognitive scar model, in which preceding posttraumatic stress symptoms adversely impact cognitions. Posttraumatic stress symptoms appear to be an important target for treatment as their reduction may help decrease internalizing and externalizing problems as well. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Asociaciones Longitudinales Entre Cogniciones Disfuncionales Relacionadas Con Maltrato Y Psicopatología En Niños Y Adolescentes COGNICIONES DISFUNCIONALES RELACIONADAS CON MALTRATATO Las cogniciones postraumáticas disfuncionales parecen jugar un papel importante en la adaptación después de experiencias traumáticas. Sin embargo, se ha realizado poca investigación en niños y adolescentes maltratados. Además, se ha investigado muy poco las posibles asociaciones causales entre cogniciones, síntomas de estrés postraumático y los problemas de internalización y externalización. En este estudio, 263 niños y adolescentes maltratados (de 8 a 17 años de edad) fueron evaluados al inicio y nuevamente en los períodos de 6 y 12 o 18 meses posteriores. Se utilizaron análisis de casos de cruce desfasado para obtener una mejor comprensión del curso y las asociaciones entre las cogniciones relacionadas con el maltrato disfuncional, los síntomas de estrés postraumático y problemas de internalización y externalización. Las calificaciones de todas las variables disminuyeron significativamente en el tiempo. Trayectorias autorregresivos moderadas a fuertes surgieron para todas las variables, denotando estabilidad. Además, las variables mostraron correlaciones moderadas a altas en cada evaluación. Los síntomas de estrés postraumático predijeron moderadamente cogniciones disfuncionales relacionados con maltrato como también los problemas de internalización y externalización 6 meses después de la evaluación inicial. Trayectorias de cruce desfasado de las cogniciones, como de los problemas de internalización y externalización a todas las demás variables no fueron significativas. Las características de edad, género y maltrato no jugaron un papel relevante en estas asociaciones de cruce desfasado cuando se incluyeron como covariables. Nuestros resultados destacan el modelo de cicatriz cognitiva, en el que los síntomas de estrés postraumático precedente afectan negativamente las cogniciones. Los síntomas de estrés postraumático parecen ser una un objetivo importante para el tratamiento, ya que su reducción puede también ayudar a disminuir los problemas de internalización y de externalización. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Longitudinal Associations between Dysfunctional Maltreatment‐Related Cognitions and Psychopathology in Children and Adolescents Traditional Chinese 標題: 兒童和青少年中, 受虐相關的認知功能失調與精神病理學的縱貫關連 撮要: 創傷後認知功能失調似乎對個人受創後適應有重要影響。可是, 少有這方面的研究專注於受虐兒童和青少年。而且, 過往亦少有研究檢視認知、創傷後壓力症狀、內化和外化行為問題之間潛在的因果關連。本研究樣本為263名受虐兒童和青少年(8–17歲)。他們分別於基線、6個月及12或18個月後接受評估。我們採用延宕交叉追蹤分析, 以理解受虐相關的認知功能失調、創傷後壓力症狀、內化和外化問題之間的發展過程和關連。所有變量的分數都隨時間顯著下降。所有變量均出現中等至強勁的自我迴歸路徑, 反映穩定性。此外, 變量在所有評估中亦顯示有中等至高水平的關連。創傷後壓力症狀在6個月後, 中等地預測到受虐相關的認知功能失調及內化和外化問題。認知以及內化和外化問題, 兩者與所有其他變量的延宕交叉路徑都不顯著。我們包含年齡、性別、虐待特徵作為共變量, 發現它們在這些延宕交叉關連間並無相關作用。結果凸顯出一個認知傷疤模型(cognitive scar model), 即過往的創傷後壓力症狀會對認知帶來不良影響。創傷後壓力症狀似乎是重要的治療目標, 因為它的減少亦能導致內化和外化問題減少。 Simplified Chinese 标题: 儿童和青少年中, 受虐相关的认知功能失调与精神病理学的纵贯关连 撮要: 创伤后认知功能失调似乎对个人受创后适应有重要影响。可是, 少有这方面的研究专注于受虐儿童和青少年。而且, 过往亦少有研究检视认知、创伤后压力症状、内化和外化行为问题之间潜在的因果关连。本研究样本为263名受虐儿童和青少年(8–17岁)。他们分别于基线、6个月及12或18个月后接受评估。我们采用延宕交叉追踪分析, 以理解受虐相关的认知功能失调、创伤后压力症状、内化和外化问题之间的发展过程和关连。所有变量的分数都随时间显著下降。所有变量均出现中等至强劲的自我回归路径, 反映稳定性。此外, 变量在所有评估中亦显示有中等至高水平的关连。创伤后压力症状在6个月后, 中等地预测到受虐相关的认知功能失调及内化和外化问题。认知以及内化和外化问题, 两者与所有其他变量的延宕交叉路径都不显著。我们包含年龄、性别、虐待特征作为共变量, 发现它们在这些延宕交叉关连间并无相关作用。结果凸显出一个认知伤疤模型(cognitive scar model), 即过往的创伤后压力症状会对认知带来不良影响。创伤后压力症状似乎是重要的治疗目标, 因为它的减少亦能导致内化和外化问题减少。